ANALISIS KESULITAN BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII PADA MATERI ALJABAR BERKAITAN DENGAN KONSEP DAN PRINSIP DI SMP PEMBANGUNAN LABORATORIUM UNP PADANG - Meisy Anggraeni (Jurnal Edukasi dan Penelitian Matematika, 2022)
The aims of this study is to find out (1) the difficulties experienced by students in class VII SMP Pembangunan Laboratorium UNP in solving problems algebra related to concepts and principles (2) factors that cause learning difficulties for class VII students of SMP Pembangunan Laboratorium UNP in learning algebra. In this study, 51 students took the test. From the results of the algebra test, none of the students' scores pass the KBM (Minimum Learning Criteria). Data were collected by algebraic test methods, questionnaires and interviews. The analytical method used is descriptive qualitative analysis. The results showed that: (1) the difficulties experienced by students of class VII SMP UNP Laboratory Development in solving algebra problems related to concepts and principles were (a) in mastering concepts, students still experienced many difficulties in all indicators, especially in considering one or more conditions required for two or more tribes to be declared as similar tribes, where the difficulty is in the very high category, namely 100%; (b) in mastering principles, students still have difficulty using the rules of algebraic operations, determining the models and methods used, and applying existing principles, which are at a very high indicator of 98.04%; (2) the factors that cause learning difficulties for students of SMP UNP Laboratory Development in studying algebra come from internal factors, namely aspects of talent and intelligence as well as external factors, namely the use of teaching aids by educators. Keywords – Types of  Mathematics Learning Difficulties, Factors Causing Difficulties, Algebra